2003
DOI: 10.1002/bjs.4080
|View full text |Cite
|
Sign up to set email alerts
|

Serum antigen(s) drive the proinflammatory T cell response in acute pancreatitis

Abstract: Acute pancreatitis results in the systemic activation of T cells. These cells are primed for a proinflammatory response to antigen stimulation and can be inhibited by antigen-specific T cell blockade. These data indicate that the immunoinflammatory response in acute pancreatitis is fueled by one or more serum antigens and offer prospects for further understanding of the aetiogenesis of pancreatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 30 publications
2
19
0
Order By: Relevance
“…In contrast to the normal 0·1 per cent T cell response to antigen, superantigens including SEB may activate up to 30 per cent of human T cells 13 , a feature consistent with the findings of the present study. A similar serum antigen effect on T cells occurs in patients with acute pancreatitis 21 , but the nature of the activating serum factor in both experimental models requires further study. The hypothesis that this involves gut hypoxia, ischaemia-reperfusion and the intraoperative generation of splanchnic cytokines seems attractive, as the gut is incriminated in the modem paradigm of SIRS and MODS, possibly through bacterial translocation or through the cytokine-generating capacity of the gut lymphoid tissue in response to injury 22 -24 .…”
Section: Discussionmentioning
confidence: 92%
“…In contrast to the normal 0·1 per cent T cell response to antigen, superantigens including SEB may activate up to 30 per cent of human T cells 13 , a feature consistent with the findings of the present study. A similar serum antigen effect on T cells occurs in patients with acute pancreatitis 21 , but the nature of the activating serum factor in both experimental models requires further study. The hypothesis that this involves gut hypoxia, ischaemia-reperfusion and the intraoperative generation of splanchnic cytokines seems attractive, as the gut is incriminated in the modem paradigm of SIRS and MODS, possibly through bacterial translocation or through the cytokine-generating capacity of the gut lymphoid tissue in response to injury 22 -24 .…”
Section: Discussionmentioning
confidence: 92%
“…[31][32][33][34] The systematic activation of T cells has also been described early in AP. 35 Although AICD has not explicitly been studied in AP, apoptosis in spleens was described in rats with severe AP induced by retrograde taurocholate infusion 36 but, as far as we know, not in the cerulein model. Of note, p8 possesses strong antiapoptotic properties.…”
Section: Discussionmentioning
confidence: 98%
“…Few studies have demonstrated the reduction of total peripheral lymphocytes as well as CD4+, CD8+, CD3+DR-and CD3-DR+ lymphocyte subsets in early severe AP [7][8][9][10] . In the most recent study, T cell activation has been reported in mild acute pancreatitis [11] . Another study showed that treatment with high-dose vitamin C partially restored depleted peripheral blood CD4+ cells and increased the ratio of CD4+/CD8+ cells [12] .…”
Section: Introductionmentioning
confidence: 99%